2020
DOI: 10.1021/acs.jproteome.0c00394
|View full text |Cite
|
Sign up to set email alerts
|

Cell Metabolomics Reveals Berberine-Inhibited Pancreatic Cancer Cell Viability and Metastasis by Regulating Citrate Metabolism

Abstract: Pancreatic cancer (PC) is becoming one of the deadliest cancers, with mortality among the highest worldwide because of its pathogenic latency and the lack of efficient drugs in the clinic. Considering that cancer cells undergo proliferation and differentiation at substantial metabolic costs, as indicated by dysregulated glycolysis and an abnormal TCA cycle induced by mitochondrial damage, we investigated the therapeutic capacity of berberine (BBR) in pancreatic cancer using a cell metabolomics method. A phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…Based on a phenotypic assay, berberine showed a notable inhibitory role in pancreatic cancer cell metastasis and viability. Additionally, berberine treatment significantly damaged the mitochondria of pancreatic cancer cells and therefore dysregulated their energy metabolism processes [ 72 ]. In pancreatic cancer cells, BBR treatment also influenced citrate metabolism resulting in blocking of the fatty acid biosynthesis.…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…Based on a phenotypic assay, berberine showed a notable inhibitory role in pancreatic cancer cell metastasis and viability. Additionally, berberine treatment significantly damaged the mitochondria of pancreatic cancer cells and therefore dysregulated their energy metabolism processes [ 72 ]. In pancreatic cancer cells, BBR treatment also influenced citrate metabolism resulting in blocking of the fatty acid biosynthesis.…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…40 Berberine is also an important component of ZJP, and recent cell metabolomics studies have revealed that berberine decreases pancreatic cancer cell viability and inhibits metastasis by regulating citric acid metabolism. 41 Furthermore, liposomes delivering both berberine and irinotecan were more effective and exhibited lower intestinal toxicity in the treatment of pancreatic cancer than liposomes delivering either component alone. 42 All of the above studies support our network pharmacological prediction and prove the feasibility of network pharmacological methods in the study of the mechanism of action of TCM.…”
Section: Discussionmentioning
confidence: 99%
“…113,114,118 Berberine is also able to trigger the extrinsic pathway of apoptosis stimulated by TRAIL, FADD, FASL and TNFα that activates caspases 8/7/3 and PARP. 155 Berberine stimulates necrosis by elevating the release of Cyp-D from mitochondria and promoting the translocation of p53 into mitochondria (Fig. 2).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Berberine treatment also increased amino acids, nucleotides metabolism and glycolysis, but reduced citric acid cycle metabolites and damaged the mitochondria (Table 1). 155…”
Section: Pancreatic Cancermentioning
confidence: 99%